Stakeholder Management in Developing a Sustainable Tourism Village Based on Renewable Energy Using RACI Matrix - Ma'arif, Syamsul; Putrianti, Flora Grace; Indraswari, Nurul Myristica; Nhu, Dương Quế; Pujianingsih, Esti Dwi; Marsinta, Ana Kardiya; Ardianti, Pipit (Journal of Industrial System Engineering and Management, 2023)
The tourism village offers cultural, natural, and authentic culinary experiences, but the growth of tourism villages must be managed sustainably to address adverse environmental impacts. Stakeholder management becomes a critical factor in planning a sustainable energy-based tourism village development project. This research aims to identify key stakeholders in the development project of the "Kampung Emas" tourism village based on renewable energy, understand their roles and responsibilities, and formulate stakeholder management strategies. The research was conducted by interviewing key stakeholders in the project and analyzing the results using the RACI Matrix table. The analysis identified four main stakeholders: the Village Head, the Tourism Awareness Group Chair, the Restaurant Manager, and the Academician. The Village Head plays a strategic role as the information disseminator at the village level; the Tourism Awareness Group Chair is fully responsible for the critical phases of the project, the Restaurant Manager has responsibilities in technical and strategic tasks, and the Academician contributes significantly to the analysis of each task. The proposed stakeholder management strategy positions the Village Head as an information disseminator, the Tourism Awareness Group Chair as the primary spokesperson, the Restaurant Manager in strategic decision-making, and the Academician as a consultative partner. This approach is expected to support successfully implementing the renewable energy-based tourism village development project.